HUBUNGAN SEBARAN MEDIA LEAFLET GIZI SEIMBANG DENGAN PERILAKU PEMILIHAN JAJANAN SEHAT PADA ANAK SEKOLAH - Kanang, Bau; Rumagia, Djilfa; Mayang, Sitti (Journal Of Midwifery And Nursing Studies, 2025)
Background: Snack selection behavior among school children is still largely influenced by environmental factors and a lack of understanding of balanced nutrition. Leaflets are one of the educational media that are easily distributed and understood by students. However, the effectiveness of balanced nutrition leaflet distribution on changing healthy snack selection behavior still needs to be studied. Objective: This study aims to determine the relationship between the distribution of balanced nutrition leaflets and healthy snack selection behavior among school children at SMK Negeri 2 Nabire. Method: This study used an analytical design with a cross-sectional approach. The study population was all grade X students of SMK Negeri 2 Nabire, with a sample of 79 respondents selected using the total sampling technique. Data collection was carried out using a structured questionnaire. Data analysis used the chi-square statistical test. Results: The results showed that students who received and understood the balanced nutrition leaflet tended to have better healthy snack selection behaviors than students who were less exposed to the leaflet. Statistical tests showed a significant relationship between the distribution of the balanced nutrition leaflet and healthy snack selection behaviors (p < 0.04). Conclusion: There is a significant relationship between the distribution of the balanced nutrition leaflet and healthy snack selection behaviors among schoolchildren at SMK Negeri 2 Nabire.